Evaluation Of Coriander (Coriandrum sativum L.) Genotypes For Seed Yield And Yield Contributing Characters (Bangladesh Journal of Agricultural Research, 2013)
Fourteen genotypes of coriander (Coriandrum sativum L.) from diversed sources were evaluated at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during the rabi season of 2007 to 2008 to select the promising genotype (s) for higher seed yield. The genotype CS005 took the minimum days for bolting (38.00), while CS003 took the maximum (60.00 days) which developed 50% most early flowers (134.3 days) and the tallest plant (116.10 cm). The maximum number of primary and secondary branches were obtained from CS004 (8.70/plant) and CS001 (15.41/plant), respectively. Umbels/plant ranged from 12.70 (CS010) to 33.37 (CS003), while umbellates/ umbel ranged from 4.75 (CS003) to 6.67 (CS010). The maximum number of seeds were obtained from CS011 (35.63/umbel and 684.3/plant) and the lowest per umbel from CS005 (15.00) and per plant from CS010 (163.3). The highest fruit set was obtained from CS011 (48.20%) followed by that of CS007 (46.30%). The genotype CS002 had the maximum 1000-seed weight (12.00 g) and CS004 the minimum (1.65 g). The genotypes CS011 and CS007 gave the highest seed yield per plant (5.79 and 5.57g) as well as per hectare (1.34 and 1.05 t). The highest germination of seed was recorded in CS003 (84.4%) and the lowest in CS004 (67.96%). The genotypes CS004, CS005, CS010, CS013, and CS014 were attacked with stem gall disease. It might be concluded from the study that the genotypes differed significantly in most of the parameters and offer a good scope of selection of better genotypes for desired traits. Bangladesh J. Agril. Res. 38(2): 189-202, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15882